PPa electroplating tail pipe part and production process thereof

CN116219512BActive Publication Date: 2026-10-09NINGBO SWELL IND CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202211565173.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-07
Publication Date
2026-10-09
Estimated Expiration
2042-12-07

AI Technical Summary

Technical Problem

[0006]为了改善PPA注塑件基体与电镀层之间结合力差、温度冲击后容易起泡的问题,本申请提供一种PPA电镀尾管零件及其生产工艺

Benefits of technology

1、由于本申请采用改性PPA材料注塑成型制备汽车尾喉外部饰圈,一方面PPA材料具有较佳的力学性能,可以替代金属材质,满足轻量化的要求。并且,采用电镀前和电镀后高温烘烤的特殊电镀工艺,大大提升了电镀层与PPA注塑件表面的结合力,减少工件受到热冲击后镀层发生起泡的现象。

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The application relates to the technical field of PPA electroplating material production, and particularly discloses a PPA electroplated tail pipe part and a production process thereof. The production process of the PPA electroplated tail pipe part comprises the following steps: S1, hanging; S2, cleaning; S3, roughening; S4, neutralization; S5, catalysis; S6, activation, acid pickling activation is carried out on the PPA injection molded part after the step S5 treatment; S7, chemical nickel plating, chemical nickel plating is carried out on the PPA injection molded part after the step S5 treatment to form a conductive layer; S8, electroplating, electroplating treatment is carried out on the surface of the conductive layer, 2-3.5 h of baking at 120-140 DEG C is carried out before electroplating, 1.5-2.5 h of baking at 120-140 DEG C is carried out after electroplating, and a copper plating layer, a nickel plating layer and a chromium plating layer are sequentially formed to obtain the PPA electroplated tail pipe part. The PPA electroplated tail pipe part has the advantages of light weight, good mechanical properties and a plating layer not prone to blistering.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of automotive PPA tailpipe technology, and more specifically, to a PPA electroplated tailpipe part and its manufacturing process. Background Technology

[0002] A car exhaust tip, also known as an exhaust pipe sleeve, is a trim piece installed at the end of the exhaust pipe. It typically consists of the tip body and an outer trim ring, and serves to prevent exhaust pipe deformation, boost pressure, and reduce noise. Car exhaust tips are usually made of stainless steel or galvanized steel, making them quite heavy, which contradicts the automotive industry's increasing trend towards lightweight design.

[0003] Currently, technicians are using engineering plastics to replace stainless steel or galvanized materials in the manufacture of exhaust tip bodies and external trim rings. For example, they are using materials such as ABS, PC / ABS, PPA, and polyoxymethylene to create corresponding injection molded parts, which have advantages such as low density, high chemical stability, and ease of processing and molding. However, for automotive exhaust tips and external trim rings, good thermal stability and mechanical properties are required. Therefore, these engineering plastics are usually modified, with the addition of glass fiber and fillers to improve the material's strength, heat resistance, and dimensional stability.

[0004] Furthermore, to achieve better aesthetics, technicians will perform electroplating on the outer surface of the injection molded parts, forming metallic plating layers such as nickel plating, copper plating, and chromium plating. This not only improves the corrosion resistance of the injection molded parts, reducing the erosion caused by external corrosive media, but also provides a better visual appearance, achieving a glossy, mirror-like finish.

[0005] Injection molded parts made of materials such as ABS, PC / ABS, and PPA often have poor adhesion between the electroplated layer and the injection molded part body due to the addition of glass fiber and fillers, as well as the physicochemical properties of the materials themselves. This is especially true when subjected to rapid heating and cooling conditions, which can easily lead to blistering. Summary of the Invention

[0006] In order to improve the problems of poor adhesion between the PPA injection molded parts and the electroplating layer and easy blistering after temperature shock, this application provides a PPA electroplated tail tube part and its manufacturing process.

[0007] In a first aspect, this application provides a manufacturing process for PPA electroplated tailpipe parts, employing the following technical solution: A manufacturing process for PPA electroplated tailpipe parts includes the following steps: S1: Hanging: Fix the PPA injection molded part to the conductive tooling to maintain good contact; S2: Cleaning: Remove oil and dust from the surface of PPA injection molded parts; S3: Roughening: Chromic acid is used to roughen the surface of PPA injection molded parts to form a microporous structure; S4: Neutralization: Remove residual chromic acid from the microporous structure after roughening in step S3; S5: Catalysis: Immerse the PPA injection molded part after step S4 into the palladium catalytic solution to fully adsorb colloidal palladium in the microporous structure; S6: Activation: The PPA injection molded parts treated in step S5 are pickled and activated. S7: Chemical nickel plating: Chemical nickel plating is performed on the PPA injection molded parts after step S5 to form a conductive layer. S8: Electroplating: Electroplating is performed on the surface of the conductive layer. Before electroplating, the surface is baked at 120-140℃ for 2-3.5 hours, and after electroplating, it is baked at 120-140℃ for 1.5-2.5 hours. The copper plating layer, nickel plating layer, and chromium plating layer are formed in sequence.

[0008] Preferably, the PPA injection molded part is one of the tailpipe body and the outer decorative ring.

[0009] More preferably, in this application, the PPA injection molded part is the outer trim ring of an automobile exhaust tip.

[0010] By adopting the above technical solution and using PPA injection molded parts as external decorative rings, a lightweight effect can be achieved. Furthermore, the PPA material is infused with glass fiber and fillers, which improves its mechanical properties and heat resistance, meeting the requirements for external decorative rings. After processes such as hanging, degreasing, roughening, neutralization, catalysis, activation, electroless nickel plating, and electroplating, a microporous roughened structure is first formed on the surface of the PPA injection molded parts, increasing the adhesion between the plating layer and the workpiece surface. Then, under the catalytic action of a palladium catalyst, colloidal palladium in the solution is uniformly adsorbed within the microporous structure, forming active catalytic palladium after activation. This facilitates the adhesion of subsequent metal plating layers and increases the conductivity of the workpiece surface.

[0011] Furthermore, by employing high-temperature baking before and after electroplating, the advantages of PPA material's high flexural modulus and low linear coefficient of thermal expansion are utilized. This reduces the likelihood of excessive deformation in PPA injection molded parts when subjected to thermal shock, thus lowering the chance of coating cracking. In addition, high-temperature baking effectively releases stress in the PPA injection molded parts, reducing material shrinkage and minimizing the likelihood of coating deformation and blistering due to stress concentration.

[0012] Preferably, in step S8, the process parameters for electroplating to form the copper plating layer are: current density 2-3 A / dm², electroplating time 60-90 min, and temperature 20-30℃.

[0013] By adopting the above technical solutions, optimizing and adjusting the process parameters of copper electroplating, controlling the electrodeposition rate of copper ions, and refining the coating grains, the copper coating lattice arrangement becomes more regular, resulting in higher bonding strength with PPA injection molded parts.

[0014] Preferably, the thickness of the copper plating layer is 30-60 μm.

[0015] By adopting the above technical solution, the thickness of the copper plating layer was tested and adjusted. The good ductility and flexibility of copper increased the adhesion of the entire plating layer. Furthermore, the coefficient of thermal expansion of copper is similar to that of PPA material, which can provide good buffering after thermal shock, further reducing the probability of plating blistering.

[0016] Preferably, in step S3, the roughening time is 10-20 min and the roughening temperature is 68-70℃.

[0017] By adopting the above technical solutions, optimizing and adjusting the roughening process, the microporous structure of the PPA injection molded parts surface is improved, the specific surface area is increased, and thus the contact area between the electroplated layer and the PPA injection molded parts surface is increased, improving the bonding force between the plating layer and the workpiece, and making it less prone to blistering and detachment.

[0018] Preferably, in step S8, the thickness of the nickel plating layer is 35-65 μm.

[0019] By adopting the above technical solution, the nickel plating layer can improve the overall mechanical properties and corrosion resistance of the plating layer. On the other hand, the nickel plating layer also has good ductility and smoothness, which can work together with the copper plating layer to withstand stronger thermal shock, disperse impact stress, and reduce the probability of plating blistering.

[0020] Preferably, the nickel plating layer includes a semi-bright nickel layer and a bright nickel layer.

[0021] By adopting the above technical solutions, optimizing and adjusting the composition and electroplating process of the nickel plating layer, and using a combination of semi-bright and bright nickel plating, the mirror-like finish of the workpiece can be improved. Furthermore, because the bright nickel layer contains sulfur, its potential is lower than that of the semi-bright nickel layer, altering the corrosion direction and reducing plating damage and peeling caused by deep corrosion.

[0022] Preferably, a nickel sealing layer is provided on the bright nickel layer.

[0023] Preferably, the electroplating solution used for the nickel sealing layer contains the following components per liter: Nickel sulfate 260-320 g / L; Nickel chloride 50-80 g / L; Boric acid 50-60 g / L; Filler 10-20g / L; Brightener 1-2g / L; Wetting agent 1.5-3g / L; The remainder is water; The filler is composed of boron nitride and 4-chloro-3-sulfonamide benzoic acid in a mass ratio of (15-20):(3-6).

[0024] More preferably, the average particle size of boron nitride is 50-200 nm. More preferably, the average particle size of boron nitride is 150 nm.

[0025] Preferably, the brightener is brightener Ni-660. The wetting agent is wetting agent W-11.

[0026] By employing the above-mentioned technical solution, a filler is added to the electroplating solution. As the electroplating process continues, nickel ions in the solution are continuously electrodeposited, and boron nitride in the filler is carried into the plating layer by the nickel ions. Since boron nitride is in nanosheet form, these boron nitride nanosheets can uniformly fill the plating layer, forming a special microporous filling structure. Because boron nitride is non-conductive, when chromium is electroplated on the nickel sealing layer, on the one hand, a chromium-nickel bonded surface structure can be formed, dispersing the corrosion current and slowing down the corrosion rate. On the other hand, during the deposition process of boron nitride nanosheets, 4-chloro-3-sulfonamide benzoic acid can be adsorbed and coated on the surface of the boron nitride nanosheets, improving the deposition state and microporous filling structure of boron nitride, resulting in better adhesion between the nickel sealing layer and other plating layers. Simultaneously, it can disperse the thermal shock stress of the plating layer and reduce the occurrence of plating blistering.

[0027] Preferably, in step S7, the thickness of the conductive layer is 0.2-0.5 μm.

[0028] By adopting the above technical solution, the thickness of the conductive layer is optimized and adjusted, which improves the conductivity without adversely affecting the bonding force between the coating and the workpiece, thereby improving the stability of the overall coating structure.

[0029] Preferably, in step S1, the PPA injection molded part is manufactured using a method comprising the following steps: 1) Melt-blend the PPA raw material, the type of which is HA-4400MP; 2) Inject the melt-blended material into a molding process. The injection process is as follows: injection pressure 130-140Pa, holding pressure 40-60Pa, barrel temperature 340-350℃, and injection speed 80-100s.

[0030] Preferably, the PPA raw material is manufactured by Lotte in South Korea.

[0031] By adopting the above technical solutions, the process window for PPA material is relatively narrow. Reducing speed and pressure will cause glass fiber exposure, resulting in a dull surface and affecting electroplating performance. Furthermore, temperatures exceeding 350℃ can easily lead to material degradation, while temperatures below 330℃ make injection molding difficult. Optimizing and adjusting the injection molding process for PPA injection molded parts improves the mechanical properties of the workpiece, better meets electroplating requirements, and enhances the adhesion between the electroplated layer and the workpiece.

[0032] Secondly, this application provides a PPA electroplated tail tube part, which adopts the following technical solution: A PPA electroplated tailpipe part, manufactured using the above-mentioned process, has a superior appearance and exhibits strong adhesion between the electroplated layer and the workpiece, remaining stable even at high temperatures up to 200°C. Furthermore, the electroplated layer does not blister after thermal shock.

[0033] In summary, this application has the following beneficial effects: 1. Because this application uses modified PPA material for injection molding to prepare the automotive tailpipe exterior trim ring, PPA material has better mechanical properties and can replace metal materials to meet the requirements of lightweighting. Furthermore, the special electroplating process of high-temperature baking before and after electroplating greatly improves the adhesion between the electroplated layer and the surface of the PPA injection molded part, reducing the phenomenon of blistering of the plating layer after the workpiece is subjected to thermal shock.

[0034] 2. In this application, a special electroplating solution is preferably used for nickel sealing. On the one hand, it improves the corrosion resistance of the electroplated layer, and on the other hand, it can effectively disperse stress and provide heat insulation, further reducing the probability of blistering of the plating layer due to thermal shock.

[0035] 3. PPA injection molded parts produced using the manufacturing process of this application have good mechanical properties, meet the requirements for metal replacement, and have a strong bond between the electroplated layer and the workpiece. They are not easily deformed or blistered under thermal shock, making them very suitable for widespread application in automotive decorative parts and contributing to the lightweight development of automobiles. Detailed Implementation

[0036] The present application will be further described in detail below with reference to the embodiments.

[0037] Unless otherwise specified, the raw materials used in the embodiments and comparative examples of this application are all commercially available. Example

[0038] Example 1 In this embodiment, the PPA electroplated tailpipe part is an outer trim ring for the tailpipe, which includes a PPA injection molded part and an electroplated layer disposed on the surface of the PPA injection molded part.

[0039] The PPA injection molded part of this embodiment includes a trim ring body. The inner and outer edges of the trim ring body are folded to the same side to form a groove. The outer edge of one side of the trim ring body extends to form two mounting clips, which are fixed to the corresponding slots of the car bumper. The trim ring body is a parallelogram in shape along its projection perpendicular to its own direction, and the trim ring body has a chamfered radius.

[0040] The PPA injection molded part in this embodiment is manufactured using a method including the following steps: 1) After drying, the PPA raw material is added to the screw extruder for melt blending. The PPA raw material is HA-4400MP and the manufacturer is Lotte in South Korea. 2) The melt-blended material is injection molded. The injection molding process is as follows: injection pressure 130MPa, holding pressure 60MPa, barrel temperature 340℃, injection speed 80mm / s, and the screw used for injection molding is an alloy screw with a diameter of 80mm.

[0041] The performance parameters of the PPA raw material in this embodiment are as follows: Flexural modulus: 90000 kgf / cm 2 ; CLTE (μm / m℃, 23-80℃): 42; Tensile strength (5mm / min): 175MPa; Elongation (5mm / min): 4%; Tensile strength (5mm / min): 175MPa; Bending strength (5mm / min): 240MPa; Heat distortion temperature (1.8MPa, 4.0mm): 275℃.

[0042] The manufacturing process of the PPA electroplated tailpipe parts in this embodiment includes the following steps: S1: Hanging: Fix the PPA injection molded part on the conductive tooling to ensure good contact between the workpiece and the conductive tooling; S2: Cleaning: Clean the surface of the workpiece to remove oil, dust, sweat and other substances, and keep the surface of the workpiece clean and dry; S3: Roughening: Use CrO3 / H2SO4 as roughening liquid to roughen the surface of PPA injection molded parts at 68℃ to form a microporous structure. The roughening time is 20min. S4: Neutralization: Rinse and soak with 10% dilute hydrochloric acid to remove residual chromic acid in the microporous structure after roughening in step S3; S5: Catalysis: Using Pd(Sn)4 / HCl as palladium catalyst, the PPA injection molded parts treated in step S4 were immersed in the palladium catalyst for 3 minutes. The temperature of the palladium catalyst was 30°C, so that the colloidal palladium was fully adsorbed in the microporous structure. S6: Activation: Using 10% dilute sulfuric acid, the PPA injection molded parts treated in step S5 are pickled and activated for 3 minutes at 55°C to dissolve divalent tin ions and expose palladium with catalytic activity. S7: Chemical Nickel Plating: Chemically plate nickel to form a conductive layer on the PPA injection molded parts after step S5 for 5 minutes at 55°C, with a conductive layer thickness of 0.2 μm; then, acid activation is performed on the conductive layer using 1% dilute sulfuric acid for 30 seconds. S8: Electroplating: First, pre-plating nickel on the surface of the conductive layer. The process parameters for pre-plating nickel are: temperature 55℃, voltage 2V, time 8min. Then, electroplating is performed. The plates are baked at 120℃ for 2 hours before electroplating and at 120℃ for 1.5 hours after electroplating, forming copper, nickel, and chromium layers sequentially. The electroplating process includes the following steps: A. Copper electroplating: current density 4A / d㎡, electroplating time 45min, temperature 20℃, copper plating layer thickness 20μm, electroplating solution used is Anmet Cupracid Ultra acid copper electroplating solution. B. Nickel electroplating: current density 4A / d㎡, electroplating time 20min, temperature 50℃, nickel plating layer thickness 30μm, electroplating solution used is Anmet 802 semi-bright nickel electroplating solution. C. Chromium electroplating: Electroplating time 30s, electroplating solution used is Activator CR electroplating solution.

[0043] The PPA electroplated tail tube part of this embodiment is manufactured by the above-described production process.

[0044] Example 2 In this embodiment, the PPA electroplated tailpipe part is an outer trim ring for the tailpipe, which includes a PPA injection molded part and an electroplated layer disposed on the surface of the PPA injection molded part.

[0045] The PPA injection molded part of this embodiment includes a trim ring body. The inner and outer edges of the trim ring body are folded to the same side to form a groove. The outer edge of one side of the trim ring body extends to form two mounting clips, which are fixed to the corresponding slots of the car bumper. The trim ring body is a parallelogram in shape along its projection perpendicular to its own direction, and the trim ring body has a chamfered radius.

[0046] The PPA injection molded part in this embodiment is manufactured using a method including the following steps: 1) After drying, the PPA raw material is added to the screw extruder for melt blending. The type of PPA raw material is HA-4400MP. 2) The melt-blended material is injection molded. The injection molding process is as follows: injection pressure 140MPa, holding pressure 40MPa, barrel temperature 350℃, injection speed 100mm / s, and the screw used for injection molding is an alloy screw with a diameter of 85mm.

[0047] The performance parameters of the PPA raw material in this embodiment are the same as those in Example 1.

[0048] The manufacturing process of the PPA electroplated tailpipe parts in this embodiment includes the following steps: S1: Hanging: Fix the PPA injection molded part on the conductive tooling to ensure good contact between the workpiece and the conductive tooling; S2: Cleaning: Clean the surface of the workpiece to remove oil, dust, sweat and other substances, and keep the surface of the workpiece clean and dry; S3: Roughening: Use CrO3 / H2SO4 as roughening liquid to roughen the surface of the PPA injection molded part at 70℃ to form a microporous structure. The roughening time is 10min. S4: Neutralization: Rinse and soak with 10% dilute hydrochloric acid to remove residual chromic acid in the microporous structure after roughening in step S3; S5: Catalysis: Using Pd(Sn)4 / HCl as palladium catalyst, the PPA injection molded parts treated in step S4 were immersed in the palladium catalyst for 5 minutes. The temperature of the palladium catalyst was 30°C, so that the colloidal palladium was fully adsorbed in the microporous structure. S6: Activation: Using 10% dilute sulfuric acid, the PPA injection molded parts treated in step S5 are pickled and activated for 5 minutes at 55°C to dissolve divalent tin ions and expose palladium with catalytic activity. S7: Chemical Nickel Plating: Chemically plate nickel to form a conductive layer on the PPA injection molded parts after step S5 for 10 min at 55 °C. The thickness of the conductive layer is 0.5 μm. Then, acid activation is performed on the conductive layer using 1% dilute sulfuric acid for 30 s. S8: Electroplating: First, pre-plating nickel on the surface of the conductive layer. The process parameters for pre-plating nickel are: temperature 55℃, voltage 2V, time 8min. Then, electroplating is performed. The plates are baked at 140℃ for 3.5 hours before electroplating and at 140℃ for 2.5 hours after electroplating, forming copper, nickel, and chromium layers sequentially. The electroplating process includes the following steps: A. Copper electroplating: Current density 2A / d㎡, electroplating time 60min, temperature 20℃, copper plating layer thickness 30μm, electroplating solution used is Anmet Cupracid Ultra acid copper electroplating solution. B. Nickel electroplating: current density 4A / d㎡, electroplating time 20min, temperature 50℃, nickel plating layer thickness 35μm, electroplating solution is Anmet 802 semi-bright nickel electroplating solution. C. Chromium electroplating: Electroplating time 30s, electroplating solution used is Activator CR electroplating solution.

[0049] The PPA electroplated tail tube part of this embodiment is manufactured by the above-described production process.

[0050] Example 3 In this embodiment, the PPA electroplated tailpipe part is an outer trim ring for the tailpipe, which includes a PPA injection molded part and an electroplated layer disposed on the surface of the PPA injection molded part.

[0051] The PPA injection molded part of this embodiment includes a trim ring body. The inner and outer edges of the trim ring body are folded to the same side to form a groove. The outer edge of one side of the trim ring body extends to form two mounting clips, which are fixed to the corresponding slots of the car bumper. The trim ring body is a parallelogram in shape along its projection perpendicular to its own direction, and the trim ring body has a chamfered radius.

[0052] The PPA injection molded part in this embodiment is manufactured using a method including the following steps: 1) After drying, the PPA raw material is added to the screw extruder for melt blending. The type of PPA raw material is HA-4400MP. 2) The melt-blended material is injection molded. The injection molding process is as follows: injection pressure 135MPa, holding pressure 50MPa, barrel temperature 350℃, injection speed 95mm / s, and the screw used for injection molding is an alloy screw with a diameter of 85mm.

[0053] The performance parameters of the PPA raw material in this embodiment are the same as those in Example 1.

[0054] The manufacturing process of the PPA electroplated tailpipe parts in this embodiment includes the following steps: S1: Hanging: Fix the PPA injection molded part on the conductive tooling to ensure good contact between the workpiece and the conductive tooling; S2: Cleaning: Clean the surface of the workpiece to remove oil, dust, sweat and other substances, and keep the surface of the workpiece clean and dry; S3: Roughening: Use CrO3 / H2SO4 as roughening liquid to roughen the surface of PPA injection molded parts at 69℃ to form a microporous structure, and the roughening time is 15min. S4: Neutralization: Rinse and soak with 10% dilute hydrochloric acid to remove residual chromic acid in the microporous structure after roughening in step S3; S5: Catalysis: Using Pd(Sn)4 / HCl as palladium catalyst, the PPA injection molded parts treated in step S4 were immersed in the palladium catalyst for 5 minutes. The temperature of the palladium catalyst was 30°C, so that the colloidal palladium was fully adsorbed in the microporous structure. S6: Activation: Using 10% dilute sulfuric acid, the PPA injection molded parts treated in step S5 are pickled and activated for 8 minutes at 55°C to dissolve divalent tin ions and expose palladium with catalytic activity. S7: Chemical Nickel Plating: Chemically plate nickel to form a conductive layer on the PPA injection molded parts after step S5 for 8 minutes at 55°C, with a conductive layer thickness of 0.35 μm; then, acid activation is performed on the conductive layer using 1% dilute sulfuric acid for 30 seconds. S8: Electroplating: First, pre-plating nickel on the surface of the conductive layer. The process parameters for pre-plating nickel are: temperature 55℃, voltage 2V, time 8min. Then, electroplating is performed. The plates are baked at 130℃ for 2 hours before and after electroplating, forming copper, nickel, and chromium layers sequentially. The electroplating process includes the following steps: A. Copper electroplating: Current density 3A / d㎡, electroplating time 90min, temperature 30℃, copper plating layer thickness 60μm, electroplating solution used is Anmet Cupracid Ultra acid copper electroplating solution. B. Nickel electroplating: current density 4A / d㎡, electroplating time 60min, temperature 52℃, nickel plating layer thickness 65μm, electroplating solution used is Anmet 802 semi-bright nickel electroplating solution; C. Chromium electroplating: Electroplating time 30s, electroplating solution used is Activator CR electroplating solution.

[0055] The PPA electroplated tail tube part of this embodiment is manufactured by the above-described production process.

[0056] Example 4 The difference between the manufacturing process of the PPA electroplated tail tube parts in this embodiment and that in embodiment 3 is: In step S8: A. Copper electroplating: current density 2.5A / d㎡, electroplating time 90min, temperature 30℃, copper plating layer thickness 50μm, electroplating solution used is Anmet Cupracid Ultra acid copper electroplating solution; B. Nickel electroplating: current density 4A / d㎡, electroplating time 40min, temperature 52℃, nickel plating layer thickness 55μm, electroplating solution used is Anmet 802 semi-bright nickel electroplating solution; The rest is the same as in Example 3.

[0057] Example 5 The difference between the manufacturing process of the PPA electroplated tailpipe parts in this embodiment and that in embodiment 4 is: In step S8: B. Electroplating of nickel: The nickel plating layer includes a semi-bright nickel layer and a bright nickel layer, obtained using the following process: b1. Semi-bright nickel layer: current density 4A / d㎡, electroplating time 18min, temperature 52℃, nickel layer thickness 23.8μm, electroplating solution used is Anmet 802 semi-bright nickel electroplating solution; b2. Bright nickel layer: current density 4A / d㎡, electroplating time 10min, temperature 52℃, nickel layer thickness 16.6μm, electroplating solution used is Unibrite 2002 bright nickel electroplating solution; The rest is the same as in Example 4.

[0058] Example 6 The difference between the manufacturing process of the PPA electroplated tailpipe parts in this embodiment and that in embodiment 4 is: In step S8: B. Electroplating of nickel: The nickel plating layer includes a semi-bright nickel layer and a bright nickel layer, obtained using the following process: b1. Semi-bright nickel layer: current density 4A / d㎡, electroplating time 18min, temperature 52℃, nickel layer thickness 27.1μm, electroplating solution used is Anmet 802 semi-bright nickel electroplating solution; b2. Bright nickel layer: current density 4A / d㎡, electroplating time 10min, temperature 52℃, nickel layer thickness 18.8μm, electroplating solution used is Unibrite 2002 bright nickel electroplating solution; The rest is the same as in Example 4.

[0059] Example 7 The difference between the manufacturing process of the PPA electroplated tail tube parts in this embodiment and that in embodiment 6 is: In step S8: B. Electroplating of nickel: The nickel plating layer includes a semi-bright nickel layer, a bright nickel layer, and a nickel sealing layer, which is obtained using the following process: b1. Semi-bright nickel layer: current density 4A / d㎡, electroplating time 18min, temperature 52℃, nickel layer thickness 23.4μm, electroplating solution used is Anmet 802 semi-bright nickel electroplating solution; b2. Bright nickel layer: current density 4A / d㎡, electroplating time 10min, temperature 52℃, nickel layer thickness 20.4μm, electroplating solution used is Unibrite 2002 bright nickel electroplating solution; b3. Nickel sealing layer: current density 4A / d㎡, electroplating time 3min, temperature 52℃. The electroplating solution used for the nickel sealing layer contains the following components per liter: Nickel sulfate 260 g / L; Nickel chloride 80 g / L; Boric acid 50g / L; Filler 10g / L; Brightener 1g / L; Wetting agent 1.5 g / L; The remainder is water.

[0060] The filler is composed of boron nitride and 4-chloro-3-sulfonamide benzoic acid in a mass ratio of 20:6.

[0061] The boron nitride has an average particle size of 150 nm. The brightener is Ni-660. The wetting agent is W-11.

[0062] The rest is the same as in Example 6.

[0063] Example 8 The difference between the manufacturing process of the PPA electroplated tail tube parts in this embodiment and that in embodiment 6 is: In step S8: B. Electroplating of nickel: The nickel plating layer includes a semi-bright nickel layer, a bright nickel layer, and a nickel sealing layer, which is obtained using the following process: b1. Semi-bright nickel layer: current density 4A / d㎡, electroplating time 18min, temperature 52℃, nickel layer thickness 23.4μm, electroplating solution used is Anmet 802 semi-bright nickel electroplating solution; b2. Bright nickel layer: current density 4A / d㎡, electroplating time 10min, temperature 52℃, nickel layer thickness 20.4μm, electroplating solution used is Unibrite 2002 bright nickel electroplating solution; b3. Nickel sealing layer: current density 4A / d㎡, electroplating time 3min, temperature 52℃. The electroplating solution used for the nickel sealing layer contains the following components per liter: Nickel sulfate 320 g / L; Nickel chloride 50 g / L; Boric acid 60g / L; Filler 20g / L; Brightener 2g / L; Wetting agent 3g / L; The remainder is water.

[0064] The filler is composed of boron nitride and 4-chloro-3-sulfonamide benzoic acid in a mass ratio of 15:3.

[0065] The boron nitride has an average particle size of 150 nm. The brightener is Ni-660. The wetting agent is W-11.

[0066] The rest is the same as in Example 6.

[0067] Comparative Example Comparative Example 1 The difference between the manufacturing process of the PPA electroplated tailpipe parts in this comparative example and that in Example 3 is: In step S8, no baking treatment is performed before or after the electroplating process; the rest is the same as in Example 3.

[0068] Comparative Example 2 The difference between the manufacturing process of the PPA electroplated tailpipe parts in this comparative example and that in Example 3 is: In step S8, the product is baked at 120°C for 2 hours before electroplating, and the rest is the same as in Example 3.

[0069] Comparative Example 3 The difference between the manufacturing process of the PPA electroplated tailpipe parts in this comparative example and that in Example 3 is: In step S8, the product is baked at 120°C for 2 hours after electroplating, and the rest is the same as in Example 3.

[0070] Comparative Example 4 The difference between the manufacturing process of the PPA electroplated tailpipe parts in this comparative example and that in Example 3 is: In step S8: A. Copper electroplating: current density 2.5A / d㎡, electroplating time 25min, temperature 30℃, copper plating layer thickness 10μm, electroplating solution used is Anmet Cupracid Ultra acid copper electroplating solution; B. Nickel electroplating: current density 4A / d㎡, electroplating time 40min, temperature 52℃, nickel plating layer thickness 55μm, electroplating solution used is Anmet 802 semi-bright nickel electroplating solution; The rest is the same as in Example 3.

[0071] Comparative Example 5 The difference between the manufacturing process of the PPA electroplated tailpipe parts in this comparative example and that in Example 3 is: In step S8: A. Copper electroplating: current density 2.5A / d㎡, electroplating time 120min, temperature 30℃, copper plating layer thickness 80μm, electroplating solution used is Anmet Cupracid Ultra acid copper electroplating solution; B. Nickel electroplating: current density 4A / d㎡, electroplating time 40min, temperature 52℃, nickel plating layer thickness 55μm, electroplating solution used is Anmet 802 semi-bright nickel electroplating solution; The rest is the same as in Example 3.

[0072] Comparative Example 6 The difference between the manufacturing process of the PPA electroplated tailpipe parts in this comparative example and that in Example 6 is: In step S8: B. Electroplating of nickel: The nickel plating layer includes a semi-bright nickel layer, a bright nickel layer, and a nickel sealing layer, which is obtained using the following process: b1. Semi-bright nickel layer: current density 4A / d㎡, electroplating time 18min, temperature 52℃, nickel layer thickness 23.4μm, electroplating solution used is Anmet 802 semi-bright nickel electroplating solution; b2. Bright nickel layer: current density 4A / d㎡, electroplating time 10min, temperature 52℃, nickel layer thickness 20.4μm, electroplating solution used is Unibrite 2002 bright nickel electroplating solution; b3. Nickel sealing layer: current density 4A / d㎡, electroplating time 3min, temperature 52℃. The electroplating solution used for the nickel sealing layer contains the following components per liter: Nickel sulfate 320 g / L; Nickel chloride 50 g / L; Boric acid 60g / L; Filler 20g / L; Brightener 2g / L; Wetting agent 3g / L; The remainder is water.

[0073] The filler is boron nitride.

[0074] The boron nitride has an average particle size of 150 nm. The brightener is Ni-660. The wetting agent is W-11.

[0075] The rest is the same as in Example 6.

[0076] Comparative Example 7 The difference between the manufacturing process of the PPA electroplated tailpipe parts in this comparative example and that in Example 6 is: In step S8: B. Electroplating of nickel: The nickel plating layer includes a semi-bright nickel layer, a bright nickel layer, and a nickel sealing layer, which is obtained using the following process: b1. Semi-bright nickel layer: current density 4A / d㎡, electroplating time 18min, temperature 52℃, nickel layer thickness 23.4μm, electroplating solution used is Anmet 802 semi-bright nickel electroplating solution; b2. Bright nickel layer: current density 4A / d㎡, electroplating time 10min, temperature 52℃, nickel layer thickness 20.4μm, electroplating solution used is Unibrite 2002 bright nickel electroplating solution; b3. Nickel sealing layer: current density 4A / d㎡, electroplating time 3min, temperature 52℃. The electroplating solution used for the nickel sealing layer contains the following components per liter: Nickel sulfate 320 g / L; Nickel chloride 50 g / L; Boric acid 60g / L; Filler 20g / L; Brightener 2g / L; Wetting agent 3g / L; The remainder is water.

[0077] The filler is composed of boron nitride and citric acid in a mass ratio of 15:3.

[0078] The boron nitride has an average particle size of 150 nm. The brightener is Ni-660. The wetting agent is W-11.

[0079] The rest is the same as in Example 6.

[0080] Comparative Example 8 The difference between the manufacturing process of the PPA electroplated tailpipe parts in this comparative example and that in Example 6 is: In step S8: B. Electroplating of nickel: The nickel plating layer includes a semi-bright nickel layer, a bright nickel layer, and a nickel sealing layer, which is obtained using the following process: b1. Semi-bright nickel layer: current density 4A / d㎡, electroplating time 18min, temperature 52℃, nickel layer thickness 23.4μm, electroplating solution used is Anmet 802 semi-bright nickel electroplating solution; b2. Bright nickel layer: current density 4A / d㎡, electroplating time 10min, temperature 52℃, nickel layer thickness 20.4μm, electroplating solution used is Unibrite 2002 bright nickel electroplating solution; b3. Nickel sealing layer: current density 4A / d㎡, electroplating time 3min, temperature 52℃. The electroplating solution used for the nickel sealing layer contains the following components per liter: Nickel sulfate 320 g / L; Nickel chloride 50 g / L; Boric acid 60g / L; Filler 20g / L; Brightener 2g / L; Wetting agent 3g / L; The remainder is water.

[0081] The filler is nano-silica.

[0082] The boron nitride has an average particle size of 150 nm. The brightener is Ni-660. The wetting agent is W-11.

[0083] The rest is the same as in Example 6.

[0084] Performance testing Detection methods The adhesion of the PPA electroplated tailpipe parts from Examples 1-8 and Comparative Examples 1-8 was tested; the state of the coating after thermal cycling was also tested. Thermal cycling test conditions: 200℃×22hr, -40℃×2hr, 3 cycles. The test results are shown in Table 1.

[0085] Table 1 Performance test data of PPA electroplated tailpipe parts in Examples 1-8 and Comparative Examples 1-8 Example 1 13.1 No foaming Example 2 13.9 No foaming Example 3 14.8 No foaming Example 4 15.0 No foaming Example 5 15.8 No foaming Example 6 15.7 No foaming Example 7 16.3 No foaming Example 8 16.5 No foaming Comparative Example 1 9.2 Severity of blistering Comparative Example 2 10.6 Medium foaming Comparative Example 3 10.8 Medium foaming Comparative Example 4 11.7 Severity of blistering Comparative Example 5 12.5 Slight bubbling Comparative Example 6 15.3 No foaming Comparative Example 7 14.6 No foaming Comparative Example 8 13.3 Medium foaming Analysis of Examples 1-4 and Comparative Examples 1-3, along with Table 1, shows that using glass fiber and filler-modified PPA material as the raw material for the tailpipe trim ring results in a lower coefficient of thermal expansion, making it less prone to thermal deformation. Furthermore, the chamfering process reduces stress imbalance at structural bends, improving coating stability and reducing the likelihood of blistering. Additionally, high-temperature baking before and after electroplating eliminates internal stress in the workpiece, providing a stable substrate surface and significantly reducing blistering during thermal shock. Comparative Example 1 did not perform pre- and post-electroplating baking, Comparative Example 2 only performed pre-electroplating baking, and Comparative Example 3 only performed post-electroplating baking; none of these methods effectively eliminated stress, leading to decreased adhesion between the coating and the workpiece and a higher risk of blistering.

[0086] Furthermore, analysis of Comparative Examples 4-5 shows that the thickness of the copper plating layer has a significant impact on the adhesion between the plating layer and the workpiece. In Comparative Example 4, the copper plating layer thickness was 10 μm, which lacked sufficient ductility, resulting in the plating layer failing to effectively buffer and offset thermal shock stress, making it prone to blistering. While the copper plating layer thickness in Comparative Example 5 was 80 μm, exhibiting better ductility and buffering properties, the longer electroplating time and excessively thick plating layer made it difficult to control the copper ion deposition process, leading to an irregular lattice arrangement within the copper plating layer and poor adhesion. Therefore, selecting an appropriate copper plating layer thickness can not only improve adhesion but also reduce the likelihood of blistering.

[0087] Analysis of Examples 5-6, 7-8, and Comparative Examples 6-8, along with Table 1, shows that the electroplating process combining a semi-bright nickel layer, a bright nickel layer, and a nickel sealing layer not only improves the corrosion resistance of the coating but also enhances the stability of the coating structure, which is beneficial for dispersing and buffering thermal stress. Furthermore, the use of a filler composed of boron nitride and 4-chloro-3-sulfonamide benzoic acid can form a special microporous filling structure, which can block the penetration of external heat, reduce the temperature difference between coating layers, and disperse and buffer thermal shock stress.

[0088] It can be seen that in Comparative Example 6, using only boron nitride as a filler, the resulting microporous filling structure had poor stress dispersion and neutralization effects, leading to a decrease in coating adhesion. In Comparative Example 7, which used a combination of boron nitride and citric acid, the adhesion was significantly lower than in Example 6. In Comparative Example 8, using nano-silica as a filler not only failed to form a microporous filling structure but also resulted in a significant decrease in coating adhesion and severe blistering.

[0089] This specific embodiment is merely an explanation of this application and is not intended to limit it. After reading this specification, those skilled in the art can make modifications to this embodiment without contributing any inventive step, but such modifications are protected by patent law as long as they fall within the scope of the claims of this application.

Claims

1. A manufacturing process for PPA electroplated tailpipe parts, characterized in that, Includes the following steps: S1: Hanging: Fix the PPA injection molded part to the conductive tooling to maintain good contact; S2: Cleaning: Remove oil and dust from the surface of PPA injection molded parts; S3: Roughening: Chromic acid is used to roughen the surface of PPA injection molded parts to form a microporous structure; S4: Neutralization: Remove residual chromic acid from the microporous structure after roughening in step S3; S5: Catalysis: Immerse the PPA injection molded part after step S4 into the palladium catalytic solution to fully adsorb colloidal palladium in the microporous structure; S6: Activation: The PPA injection molded parts treated in step S5 are pickled and activated. S7: Chemical nickel plating: Chemical nickel plating is performed on the PPA injection molded parts after step S5 to form a conductive layer. S8: Electroplating: Electroplating is performed on the surface of the conductive layer. Before electroplating, the surface is baked at 120-140℃ for 2-3.5 hours, and after electroplating, it is baked at 120-140℃ for 1.5-2.5 hours. The copper plating layer, nickel plating layer, and chromium plating layer are formed in sequence. In step S8, the thickness of the nickel plating layer is 35-65 μm; The nickel plating layer includes a semi-bright nickel layer and a bright nickel layer; A nickel sealing layer is provided on the bright nickel layer; The electroplating solution used for the nickel sealing layer contains the following components per liter: Nickel sulfate 260-320 g / L; nickel chloride 50-80 g / L; boric acid 50-60 g / L; filler 10-20 g / L; brightener 1-2 g / L; wetting agent 1.5-3 g / L; balance: water; The filler is composed of boron nitride and 4-chloro-3-sulfonamide benzoic acid in a mass ratio of (15-20):(3-6).

2. The manufacturing process for a PPA electroplated tailpipe part according to claim 1, characterized in that, In step S8, the process parameters for electroplating to form the copper plating layer are: current density 2-3A / dm², electroplating time 60-90min, and temperature 20-30℃.

3. The manufacturing process for a PPA electroplated tailpipe part according to claim 2, characterized in that, The thickness of the copper plating layer is 30-60 μm.

4. The manufacturing process for a PPA electroplated tailpipe part according to claim 1, characterized in that, In step S3, the roughening time is 10-20 min and the roughening temperature is 68-70℃.

5. The manufacturing process for a PPA electroplated tailpipe part according to claim 1, characterized in that, In step S7, the thickness of the conductive layer is 0.2-0.5 μm.

6. The manufacturing process for a PPA electroplated tailpipe part according to claim 1, characterized in that, In step S1, the PPA injection molded part is manufactured using a method comprising the following steps: 1) The PPA raw material, model HA-4400MP, is melt-blended. 2) Inject the melt-blended material into a mold. The injection molding process is as follows: injection pressure 130-140MPa, holding pressure 40-60MPa, barrel temperature 340-350℃, and injection speed 80-100mm / s.

7. A PPA electroplated tail tube part manufactured by a process described in any one of claims 1-6.

Citation Information

Patent Citations

  • Plastic plating method for automobile component

    CN104499019A

  • Automobile tailgate exhaust pipe

    CN109435683A

  • Method for plating plastic

    JP1989123093A

  • Metal-clad laminate, and method for production of metal-clad laminate

    WO2008123036A1